# MATHS~~20POINTS

SIMPLIFY

1. (2x/x^2-1)-(1/x-1)-(1/x+1)

2. a= 1-x^2 b=1+x express 4 in terns of b

3.(5x+2)[(5x/2) -1]

Rating

1. (2x/x^2-1)-(1/x-1)-(1/x+1)

= 2/x - 1 - 1/x + 1 - 1/x - 1

= (2-1-1)/x -1+1-1

= 0-1+1-1

= -1

2. a= 1-x^2

b=1+x

express 4 in terns of b (i suppose u are asking "express a in terms of b")

b = 1+x

b-1 = 1+x-1

x = b-1

a = 1-x^2

= 1 - (b-1)^2

= 1 - [b^2 - 2(b)(1) + (-1)]

= 1 -b^2 + 2b + 1

= -b^2 + 2b + 2

So, a = -b^2 + 2b + 2.

3.(5x+2)[(5x/2) -1]

= 5x(5x/2) - 5x + 2(5x/2) - 2

= (25x^2)/2 -5x + 5x - 2

= (25x^2)/2 - 2

2008-10-19 21:30:27 補充：

a = 1-x^2

= 1 - (b-1)^2

= 1 - [b^2 - 2(b)(1) + (-1)] <-- sorry i made mistake here

= 1 - b^2 + 2b + 1

= -b^2 + 2b + 2

So, a = -b^2 + 2b + 2.

should be

= 1 - [b^2 - 2(b)(1) + (-1)^2]

= 1 - b^2 + 2b - 1

= - b^2 + 2b

So, a in terms of b is - b^2 + 2b. =)

• (2x/x^2-1)-(1/x-1)-(1/x+1)

=[2x-(x+1)-(x-1)]/(x^2-1)

=(2x-x-1-x+1)/(x^2-1)

=0//

a= 1-x^2 b=1+x express a in terns of b

a= 1-x^2

x=sqrt(1-a)

then sub x=sqrt(1-a) into b=1+x

b=sqrt(1-a)+1//

(5x+2)[(5x/2) -1]

=(5x+2)(5x-2)/2

=(25x^2-4)/2//